Pengaruh Persepsi Risiko terhadap Minat Beli Online dengan Kepercayaan sebagai Variabel Mediasi (Studi pada Konsumen KoreaBuys.com) - Rizkitasari, Fairus (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research tries to identify the direct and indirect influence of perceived risk on online purchase intention of customers of KoreanBuys.com mediated by trust. This explanatory research explains the causal relationship between the variables through hypothesis testing.Using non-probability sampling technique with the criteria of people who are at least 17 years of age and people who know and have accessed KoreaBuys.com, 130 people were selected as the respondents. The hypotheses were assessed using t test and Sobel test. The data were analyzed through Partial Least Squares (PLS) using SmartPLS 3.0.The results of the hypothesis testing show that perceived risk negatively and significantly affects trust, that perceived risk negatively and significantly affects online purchase intention, that trust positively and significantly affects online purchase intention, and that perceived risk positively and significantly affects online purchase intention mediated by trust.Keywords: perceived risk, online purchase intention, trust